Comparison between transmission control protocol schemes on wireless environment - M. Albareki, Mustafa Ali (2008)
Transmission Control Protocol (TCP) is reliable transmission protocol. It resides on the transport layer in the TCP/IP stack serving the upper application layer. Wireless networks send and receive data over the air using Radio Frequencies. That makes them vulnerable to high collisions rates and high Bit Error Rate (BER). Transmissions over wireless links suffer from delays, frequent disconnections during handoffs and collisions along with standard TCP’s congestion control mechanisms treat all errors as congestions and apply algorithms to degrade the throughput of TCP even more. In this study, wired and wireless TCP schemes are analyzed. This includes TCP-Tahoe, TCP-Reno, TCPVegas, TCP-Veno, TCP-SACK and TCP-Freeze. The TCP schemes are reviewed and several experiments are conducted. The results are then compared to check their performances regarding average throughput, average delay and their congestion window. Three different simulation environments that are considered that are Wired, Wireless and Heterogeneous using network simulator, NS-2.26 and NS-2.33. The results of the study show similarities and differences between the TCP schemes. From the simulations it is clear that in terms of packet delivery delays TCP-Vegas and TCP-Veno scored the best results in all the networks environments. They also achieved the best throughput in wired and heterogeneous networks while Freeze achieved the best throughput and congestion window in wireless (ad-hoc) environment. In wired networks TCP-SACK had the best congestion window; however, when implemented in with wireless mediums it did not perform well. Tahoe had the best congestion window in heterogeneous networks. The work for this study can be used as a reference for future researches in the area.TCP schemes such as Vegas and Veno implemented better algorithms to perform better over wireless links. TCP-Freeze which freezes all the timers and congestion window before handoffs helped improving TCP performance in mobile scenarios while proved ineffective in fixed wireless or wired scenarios.